KUALITAS PELAYANAN PRAMUWISATA BERBAHASA PERANCIS DI BALI - Ratri Paramita; Teguh Hadi Sukarno; Indah Kusumarini (JURNAL KEPARIWISATAAN, 2018)
The goal of this research is to find the quality service of French-speaking guidewhen they serve during the peak season in Bali, between Juli-Septembre. In another hand, according to the data of Bali’s Guide Office, there are only 235 among 8.198 French speaking guides who are competence and certified. The data were collected using a questionnaire with Likert Scale of degree 5. The data were analyzed using 5 dimensions of ServQual, and analyzed by comparing between the expectation and perception of tourists toward the quality services Bali’s French speaking guides which are: Tangible, Reliability, Responsiveness, Assurance and Empathy. The data also analyzed by using SPSS System version 13,0. The result of-of this analysis are: the mean score of tourist expectation of quality services Bali’s French speaking guides is in 3.46, and the men score of tourist perception of quality services Bali’s French speaking guides is in 3.29. It means that tourists are not satisfied.